Pengaruh Lama Perendaman Dan Perbedaan Metode Pengeringan Pada Pembuatan Tepung Ampas Kelapa (Cocos Nucifera L.) - Hamka Nurkaya (Jurnal Loupe, 2017)
The growth of coconut processing industry has increased the number of cocounut waste such as coconut flesh which is normally thrown away or sold as animal feed at a very low price. Production of coconut pulp flour is one way to enhance the economical value of coconut waste. The aim of this research was to find the moisture content and panelists’ preferences on coconut pulp flour obtained through two methods i.e, oven drying and sunlight drying. Soaking is an important phase in producing coconut pulp flour. In this research the effect of soaking time in of 0 hour, 1 hour, 2 hour2, and 3 hours were observed. The finding shows that 3 hour soaking and oven drying resulted in the best moisture content of 4.33%. Meanwhile, the 2 hour soaking and oven drying resulted in the highest organoleptic score for colour, aroma, and texture of 4.65, 4.23, and 4.20 respectively.